2017
DOI: 10.1186/s40463-017-0209-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with lingual tonsil hypertrophy in Canadian adults

Abstract: BackgroundHypertrophy of the lingual tonsil tissue in the adult patient is thought to contribute to the pathophysiology of obstructive sleep apnea. The underlying etiology of lingual tonsil hypertrophy (LTH) in the adult patient is unclear and likely multifactorial. Previous studies have suggested that the lingual tonsils may undergo compensatory hyperplasia post-tonsillectomy in children, although it is unknown if this occurs or persists into adulthood. The purpose of this study was to determine what factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 13 publications
0
32
1
1
Order By: Relevance
“…We also observed an overreliance on the same laryngeal signs, especially those described in RFS, and a lack of consideration of other laryngeal (i.e., vocal fold erythema, leukoplakia, and keratosis) and extralaryngeal signs (i.e., tongue tonsil hypertrophy, posterior pharyngeal wall and anterior pillars erythema, edema, coated tongue), although they seemed to concern a considerable number of patients according to previous clinical reports. 7,8,39,45,69 The lack of consideration of these signs might significantly affect the development of an instrument and its usefulness as a diagnostic tool (i.e., patient inclusion) or therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed an overreliance on the same laryngeal signs, especially those described in RFS, and a lack of consideration of other laryngeal (i.e., vocal fold erythema, leukoplakia, and keratosis) and extralaryngeal signs (i.e., tongue tonsil hypertrophy, posterior pharyngeal wall and anterior pillars erythema, edema, coated tongue), although they seemed to concern a considerable number of patients according to previous clinical reports. 7,8,39,45,69 The lack of consideration of these signs might significantly affect the development of an instrument and its usefulness as a diagnostic tool (i.e., patient inclusion) or therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It is partly for this subjective aspect that a few authors prefer to assess both frequency and intensity of each symptom with a clear definition of the corresponding rates . With regard to signs assessment, vocal fold erythema, keratosis, and a large number of extralaryngeal signs (i.e., posterior pharyngeal wall inflammation, anterior pillars inflammation, coated tongue) are not evaluated with RFS, although they concern a considerable number of patients . Moreover, some usual signs related to LPR (i.e., leukoplakia, granuloma) consisted of exclusion criteria in other studies .…”
Section: Discussionmentioning
confidence: 99%
“…60,86 With regard to signs assessment, vocal fold erythema, keratosis, and a large number of extralaryngeal signs (i.e., posterior pharyngeal wall inflammation, anterior pillars inflammation, coated tongue) are not evaluated with RFS, although they concern a considerable number of patients. 45,102,103 Moreover, some usual signs related to LPR (i.e., leukoplakia, granuloma) 102 consisted of exclusion criteria in other studies. 51 In addition, our analysis suggests that only a few authors performed blinded evaluations with regard to the patient complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Lingual tonsil hypertrophy (LTH) is a clinical condition often observed in clinical practice during the inspection of the tongue base region . This lymphatic hypertrophy (LH) is implicated in a variety of airway pathologies, ranging from sleep‐related breathing disorders, lingual tonsillitis, and difficult intubation procedures . Additionally, it is frequently a cause of foreign body sensation in the throat and of pharyngodynia in cases of it inflammation …”
Section: Introductionmentioning
confidence: 99%
“…The etiology regarding the growth of this lymphatic tissue (LT) has not been clearly proved . The few studies about this topic showed that previous adenotonsillectomy, laryngopharyngeal reflux (LPR), and a high body mass index could be correlated to LTH, even if defined data regarding this aspect are not available …”
Section: Introductionmentioning
confidence: 99%